Insulin acts as a repressive factor to inhibit the ability of PAR2 to induce islet cell transdifferentiation. Issue 6 (2nd November 2018) - Lee, Seung-Hee; Hao, Ergeng; Scharp, David; Levine, Fred
ABSTRACT: Recently, we showed that pancreatitis in the context of profound β-cell deficiency was sufficient to induce islet cell transdifferentiation. In some circumstances, this effect was sufficient to result in recovery from severe diabetes. More recently, we showed that the molecular mechanism by which pancreatitis induced β-cell neogenesis by transdifferentiation was activation of an atypical GPCR called Protease-Activated Receptor 2 (PAR2). However, the ability of PAR2 to induce transdifferentiation occurred only in the setting of profound β-cell deficiency, implying the existence of a repressive factor from those cells. Here we show that the repressor from β-cells is insulin. Treatment of primary islets with a PAR2 agonist (2fLI) in combination with inhibitors of insulin secretion and signaling was sufficient to induce insulin and PAX4 gene expression. Moreover, in primary human islets, this treatment also led to the induction of bihormonal islet cells coexpressing glucagon and insulin, a hallmark of islet cell transdifferentiation. Mechanistically, insulin inhibited the positive effect of a PAR2 agonist on insulin gene expression and also led to an increase in PAX4, which plays an important role in islet cell transdifferentiation. The studies presented here demonstrate that insulin represses transdifferentiation of α- to β-cells induced by activation of PAR2. This provides a mechanistic explanation for the observation that α- to β-cell transdifferentiation occurs only in the setting of severe β-cell ablation. The mechanistic understanding of islet cell transdifferentiation and the ability to modulate that process using available pharmacological reagents represents an important step along the path towards harnessing this novel mechanism of β-cell neogenesis as a therapy for diabetes.